Detecting Single Molecule Deoxyribonucleic Acid in a Cell Using a Three‐Dimensionally Integrated Nanopore (Small Methods 9/2021). Issue 9 (14th September 2021) - Tsutsui, Makusu; Yokota, Kazumichi; Arima, Akihide; Washio, Takashi; Baba, Yoshinobu; Kawai, Tomoji
Abstract : Inside Back Cover In article number 2100542, Tsutsui, Baba, Kawai, and co‐workers demonstrated the use of a 3D integrated nanopore system for in situ detections of single molecule proteins and DNA in a cell by ionic current. With the proven potential of nanopore sequencing, the present device technology promises amplification free genome analysis that may revolutionize biology and medicine through uncovering genetic variations at a single cell level.